Implementasi Profil Pelajar Pancasila Guna Pencegahan Tindak Perundungan Siswa - Nurhakim, Haditsa Qur'ani; Sanusi, Iwan; Nur'aeni, Ulvah; Muhammad, Giantomi (Tapis: Jurnal Penelitian Ilmiah, 2024)
The world of education is a forum where people are educated and formed in very basic ways so that they can live their lives better. Education units in Indonesia, especially at the junior high school level, are at the forefront of shaping the character of their students at school. However, the implementation of the learning process at school will not run smoothly as desired by parents and the school. When students are at school there will always be jokes with their friends, but those who speculate when joking are out of bounds. Character development is very important to change the characters of today's alpha generation which still have to be managed extraordinarily. The support from the government for the P5 Program is directly proportional to the objectives of the Pancaila principles, especially the 2nd principle. The existence of the P5 program aims to reduce cases of bullying in schools driven by the driving teachers at the school. This research method uses descriptive which defines what conditions or phenomena exist. The approach is qualitative. The results of this research are to prevent bullying among students. Bullying is a serious problem in the world of education because it can mislead students' parents.